PRELIMINARY DATA ON COAT COVERAGE AND GROOMING INTERFERING WITH THE THERMAL COMFORT OF LHASA APSO AND SHIH TZU DOGS - Felix, Gisele Aparecida; Valentim, Jean Kaique; Almeida, Alexander Alexandre de Alexandre; Mattos Silva, Dheywid Karlos; Lopes, Bruno Alves; Sunada, Natália da Silva; Fontura Mateus, Nathália Lopes; Caldara, Fabiana Ribeiro (Archives of Veterinary Science, 2024)
The objective of this report was to investigate the effects of grooming on thermal comfort in Lhasa Apso and Shih Tzu dogs exposed to different ambient temperatures. A randomized block design in a 3 x 2 factorial scheme was used, with 3 different temperatures associated with whether the animal was groomed or not. Six adult dogs, consisting of two Lhasa Apsos and four Shih Tzus, were used. The dogs were exposed to temperatures of 17°C, 25°C, and 33°C both before and after grooming. Physiological parameters (blood pressure, heart rate, respiratory rate, rectal temperature, ambient temperature, ITU, and body surface temperature) were measured using infrared thermography with a portable IRT camera. The images were analyzed using FLIR Tools™ software with an emissivity of 0.97. Variance analysis was performed to evaluate the isolated effects and interactions between the factors of coat coverage and ambient temperature at the 5% significance level. No interaction was found between the treatments, nor were there isolated effects of the factors on the physiological parameters evaluated. A temperature of 33°C was associated with a higher rectal temperature (p<0.05) in the animals. Ungroomed dogs exposed to temperatures of 25°C and 33°C had ITU values above the thermal comfort limit. In terms of body temperature, there was a significant interaction effect between coat coverage and the environment under different climatic conditions (p<0.05). The surveyed grooming dogs exhibited greater body temperatures at all temperatures tested, namely, 17°C, 25°C, and 33°C. Grooming did not reduce the effects of thermal stress caused by different climatic conditions, indicating that grooming is not advisable for these animals